Polskie Biblie XVI-wieczne – przegląd egzemplarzy, cechy charakterystyczne oraz czynniki wpływające na kształtowanie się cen na polskim rynku aukcji antykwarycznych - Zakonnik, Łukasz (The Biblical Annals, 2026)
This article discusses the copies of 16th-century Polish Bibles on the antiquarian auction market in Poland. It aims to expand the knowledge of surviving copies of old Polish Bibles, which, often, due to being held in private collections, have not been described and catalogued. This study identified 59 offers for Bible copies, with the largest number concerning the Wujek Bible. In turn, the rarest were the 1st edition of the Leopolita Bible and the Brest Bible. The descriptions were supplemented for the 2nd edition of the Leopolita Bible and a brief mention of the Budny Bible. This article also seeks to identify the factors that influenced the prices of the copies discussed earlier. The most important of these included the broadly understood condition of the copy, while the least important was the inclusion of illustrations in the editions of the Bible under discussion.